EVOLVE - A Bridge between Probability, Set Oriented Numerics, and Evolutionary Computation II - Schütze, Oliver; Coello Coello, Carlos A.; Tantar, Alexandru-Adrian.; Tantar, Emilia; Bouvry, Pascal; Del Moral, Pierre; Legrand, Pierrick; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book comprises a selection of papers from the EVOLVE 2012 held in Mexico City, Mexico. The aim of the EVOLVE is to build a bridge between probability, set oriented numerics and evolutionary computing, as to identify new common and challenging research aspects. The conference is also intended to foster a growing interest for robust and efficient methods with a sound theoretical background. EVOLVE is intended to unify theory-inspired methods and cutting-edge techniques ensuring performance guarantee factors. By gathering researchers with different backgrounds, a unified view and vocabulary can emerge where the theoretical advancements may echo in different domains. Summarizing, the EVOLVE focuses on challenging aspects arising at the passage from theory to new paradigms and aims to provide a unified view while raising questions related to reliability,  performance guarantees and modeling. The papers of the EVOLVE 2012 make a contribution to this goal. .
Part I Cell Mapping and Quasi-stationary Distributions -- Part II Genetic Programming -- Part III EvolutionaryMulti-objective Optimization -- Part IV Combinatorial Optimization -- Part V ProbabilisticModeling and Optimization for Emerging Networks -- Part VI Hybrid Probabilistic Models for Real Parameter Optimization and their Applications -- Part VII Evolutionary Computation for Vision, Graphics, and Robotics -- Part VIII Real-world Application of Bio-inspired Metaheuristics.
Keywords: Computational intelligence; Artificial intelligence; Statistics .; Neural networks (Computer science) .; Operations research; Decision making; Computational Intelligence; Artificial Intelligence; Statistics for Engineering, Physics, Computer Science, Chemistry and Earth Sciences; Mathematical Models of Cognitive Processes and Neural Networks; Operations Research/Decision Theory